Kemampuan Literasi Matematika Siswa SMP Dalam Menyelesaikan Soal Matematika Realistik - Nurhalisah, Ita Amalia; Lukman, Hamidah Suryani; Mulyanti, Yanti; Bahasa Indonesia, Bahasa Indonesia (Jurnal PEKA (Pendidikan Matematika), 2025)
Questions that can be used to measure mathematical literacy skills are realistic mathematics questions. Thus, research was conducted to identify students' mathematical literacy abilities in solving realistic mathematics problems. The research method used is a quantitative descriptive method by providing 6 questions describing material on a two-variable linear equation system that can measure mathematical literacy abilities. The results showed that 51.9% were in the low category, 18.5% were in the medium category and 29.6% were in the high category. Based on the results of students' answers, students are still less capable in interpretation and calculations using existing methods in a two-variable linear equation system, students tend to use calculations outside of these methods so that students cannot write down how the calculation process works. Based on the results of research that has been carried out, it show that the mathematical literacy abilities of junior high school students are in the low category.